Sosialisasi Meningkatkan Kesadaran Pentingnya Menabung Sejak Dini di TK Yarsi Mataram - I Nyoman Bagus Aji Kresna; Puspita Ayu, Baiq Dinda; Aryani , R . Ayu Ida; Ana Rahmatyar; Muhammad Haris Nasri (Insan Kreasi Media, 2022)
The service program is one of the obligations of the implementation of the tri dharma of higher education that must be carried out. The Bumigora University service team has successfully carried out service at Yarsi Mataram Kindergarten. This result is to increase awareness of the importance of saving from an early age, the team provides socialization through playing and singing, storytelling (media storytelling) which in the story adds to the benefits of saving for children in the future, and quizzes. Teaching the importance of saving from an early age can shape children's character, children will be more responsible for the money they have, can save more, introduce the value of money later on, children will be able to distinguish which are priority needs and which are not.